Rhabdomyolysis Caused by Gefitinib Overdose - Niimi, Kyoko; Obayashi, Shohei; Oguma, Tsuyoshi; Tanaka, Jun; Ito, Yoko; Tomomatsu, Katsuyoshi; Hayama, Naoki; Urata, Mika; Asano, Koichiro (Internal Medicine, 2022)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are common therapeutic agents for EGFR mutation-positive advanced non-small-cell lung cancer. There has been no report of rhabdomyolysis caused by an overdose of EGFR-TKIs. We herein review the existing literature on the subject and report a rare case of rhabdomyolysis due to an overdose of gefitinib, an EGFR-TKI.